Strategi Komunikasi Digital Berbasis Psikologi pada Instagram @Nuonline_id: Analisis Pendekatan Kognitif, Afektif, dan Behavioral - Disye Maulidiana Millati; Enung Asmaya (Kartika: Jurnal Studi Keislaman, 2026)
The development of social media has changed the communication patterns of organizations in building relationships with the public. Instagram, as a digital communication medium, is used not only for disseminating information but also as a means of shaping audience perceptions, emotions, and behavior. This study aims to analyze the psychology-based digital communication strategy of the Instagram account @nuonline_id through cognitive, affective, and behavioral approaches. The study used a descriptive qualitative method using observation techniques of Instagram content, documentation, and literature studies related to digital communication and communication psychology. The results show that the digital communication strategy of the @nuonline_id account is implemented through the presentation of Islamic-based educational information to build the cognitive aspects of the audience, the use of visuals and persuasive narratives to build emotional engagement in the affective aspects, and calls to social and religious action to influence the behavioral aspects of the audience. These strategies demonstrate that psychology-based digital communication can increase engagement and strengthen the image of Nahdlatul Ulama's digital da'wah media in the digital society. This study confirms that a psychology-based communication approach plays a crucial role in the effectiveness of social media communication of religious organizations.